PERBANDINGAN KELIMPAHAN DAN ASOSIASI POHON AQUILARIA MALACCENSIS LAM. DAN CASTANOPSIS ARGENTEA (BLUME) A.DC. DI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM PROVINSI RIAU - Sri Wahyuni; Mar’atul Afidah; Marta Dinata (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
According to data from the 2019 IUCN Red List, the Aquilaria malaccensis species is included in the "Critically Endangered" category and the Castanopsis argentea species is included in the "Endangered" category. This study aims to determine the comparison of abundance and associations of Aquilaria malaccensis Lam. and Castanopsis argentea (Blume) A.DC. in Sultan Syarif Hasyim Forest Park, Riau Province. Data collection is carried out by making observation plots. In this research, an observation plot will be made measuring 20 m x 20 m to analyze tree vegetation. The research plot was determined deliberately (purposive sampling) and measurements were carried out in places where there were Aquilaria malaccensis and Castanopsis argentea trees. The population in this study is the area of ​​Tahura Sultan Syarif Hasyim in Siak Regency, namely, 2,400 Ha. The sample in this study was taken with a sampling intensity of 0.1%. So, the sample in this study covers an area of ​​24,000 m2. The type of data collected is primary data consisting of data on the abundance and association (with other plants) of Aquilaria malaccensis and Castanopsis argentea in Tahura SSH, Riau Province as well as secondary data in the form of the general condition of the research location, maps and the results of research that has been carried out, thesis or journals related to the title to be researched. Data analysis in the form of an Important Value Index, Diversity Index, and associations with other types. The results of data analysis can determine the abundance and associations of Aquilaria malaccensis Lam. and Castanopsis argentea (Blume) A.DC. in Sultan Syarif Hasyim Forest Park, Riau Province. The research results show that the Castanopsis argentea species has a higher abundance of 0.03 than Aquilaria malaccensis, which is 0.003. The highest association of Castanopsis argentea was 0.5 with Palaquium burkii, while the highest association of Aquilaria malaccensis was 0.8 with Sloetia elongata.